2023
DOI: 10.3390/nu15214593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intake of Extra Virgin Olive Oil on Mortality in a South Italian Cohort with and without NAFLD

Caterina Bonfiglio,
Francesco Cuccaro,
Angelo Campanella
et al.

Abstract: Background: Extra-virgin olive oil (EVOO) is the main source of seasoning fat in the Mediterranean diet and it is one of the components with known protective factors on chronic-degenerative disease. We aimed to evaluate the effect of a medium-high level of oil consumption on mortality in a cohort with good adherence to the Mediterranean diet. Methods: A total of 2754 subjects who had completed the food questionnaire in the Multicenter Italian study on Cholelithiasis (MICOL) cohort were included in the study. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Our hypothesis is supported by the literature, and more specifically by the multiple papers that show the benefits of the Mediterranean diet in helping to prevent metabolic diseases, cancers, and cardiovascular disease [30,31], including a recent study that showed the protective effect of extra virgin olive oil on overall mortality and NAFLD [32].…”
Section: Discussionsupporting
confidence: 64%
“…Our hypothesis is supported by the literature, and more specifically by the multiple papers that show the benefits of the Mediterranean diet in helping to prevent metabolic diseases, cancers, and cardiovascular disease [30,31], including a recent study that showed the protective effect of extra virgin olive oil on overall mortality and NAFLD [32].…”
Section: Discussionsupporting
confidence: 64%
“…Table S3† shows the characteristics of the chosen articles. Of these, 24 were from Europe, 10,11,13,20,21,36–54 4 from North America, 9,12,18,19 1 from Asia, 14 and 1 covering 13 countries. 35 The sample size ranged from 673 39 to 547 183.…”
Section: Resultsmentioning
confidence: 99%
“…The study contained 14 studies (13 articles) 9,11,13,14,18,20,21,38–40,47,53,54 with 176 729 cases of all-cause mortality among 723 224 individuals. The combined RR for the categories with the highest and lowest intakes of olive oil was 0.85 (95% CI: 0.81, 0.89), with some heterogeneity ( I 2 = 88.4%, P heterogeneity < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it emerged that in the NASH group, the gene expression of the fibrotic markers tumor growth factor(TGF)-β and α-SMA was significantly increased, while the NASH+RA group showed a significant reduction in the gene expression of TGF-β and α-SMA (P < 0.05). Komeili-Movahhed et al carried out a new study on 24 C57/BL6 mice treated for 8 weeks [63] . During the experiment, the mice were divided into four groups: CO group (standard diet), RA group (standard diet and RA (10 mg/kg), NASH group (MCD diet), and NASH+ RA group (MCD + RA diet (10 mg/kg).…”
Section: Rosemarymentioning
confidence: 99%